The effect of temperature on inflorescence initiation, differentiation and development of Lachenalia cv. 'Romelia' - Holtzhausen, Lucas Cornelius (University of Pretoria, 2022)
Dissertation (MSc (Agric))--University of Pretoria, 1991.